2018
DOI: 10.1017/s1041610218001400
|View full text |Cite
|
Sign up to set email alerts
|

Management of visual hallucinations in dementia and Parkinson’s disease

Abstract: Objectives:Visual hallucinations are a common symptom in dementia and Parkinson’s disease and have been associated with greater cognitive and functional decline, but optimal management strategies are unclear. We review the frequency and pathogenesis of visual hallucinations in dementia and Parkinson’s disease and examine the evidence base for their management.Design:We undertook a systematic review of the visual hallucinations in dementia, searching studies published between January 1980 and July 2017 using Pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 119 publications
0
16
0
Order By: Relevance
“…Systematic reviews revealed that he most common psychotic symptom in idiopathic Parkinson's disease (IPD) is visual hallucination, with an estimated pooled prevalence of 28.2% (±19.1 to 39.5), followed by isolated delusions (mostly paranoid) . DRT‐induced visual hallucinations are more frequent in IPD than in patients with mutations in PD‐related genes (except for PARK‐GBA that shows similar figures) and are also commonly associated with dementia . In IPD, the content of hallucinations is often stereotyped with frequent descriptions of animals .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Systematic reviews revealed that he most common psychotic symptom in idiopathic Parkinson's disease (IPD) is visual hallucination, with an estimated pooled prevalence of 28.2% (±19.1 to 39.5), followed by isolated delusions (mostly paranoid) . DRT‐induced visual hallucinations are more frequent in IPD than in patients with mutations in PD‐related genes (except for PARK‐GBA that shows similar figures) and are also commonly associated with dementia . In IPD, the content of hallucinations is often stereotyped with frequent descriptions of animals .…”
Section: Resultsmentioning
confidence: 99%
“…Visual hallucinations commonly occur several years after disease onset and are often associated with DRT and dementia . Response to antipsychotic treatment has been only partial …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Swann and O'Brien 61 performed a systematic review of manuscripts reporting management strategies of visual hallucinations in dementia and PD. They included all study designs in their review but did prioritize RCT's or meta‐analyses.…”
Section: Discussionmentioning
confidence: 99%
“…Since these symptoms may be induced by medication (namely, dopamine agonists), dopaminergic pathways were presumably involved, but not only [Fénelon et al, 2000] [Friedman, 2010]. A number of studies have shown the benefit of acetylcholinesterase inhibitors [Burn et al, 2006] [Swann and O'Brien, 2018], suggesting involvement of the cortical cholinergic pathway. Moreover, visual dysfunction is frequent in patients with PD.…”
Section: Introductionmentioning
confidence: 99%